Technique and social complexity: development trajectories of peasant societies with metallurgy during the Bronze Age of western Iberia - Senna-Martinez, João Carlos (2018)
Technological change has been usually correlated with complexity change. Namely metallurgical practice from the ancient peasant societies was for a long time perceived as an “engine” of social development. Such a perception revealed itself not only inaccurate but it must also be seen as largely varying according to geographical place and civilization characteristics. Nevertheless, in ancient peasant societies technological development remains one of the most promising indicators of the growing of social complexity even if it is by no means the only possible one and such growth must always be analysed accordingly to regional constraints. In what concerns the Iberian Peninsula, and particularly its western facade, first metallurgies seem to appear as a consequence of socioeconomic developments leading to first social elites coming into being. The metallurgical products can then be seen to fulfil the need to express social status, lacking real technomic significance. Development of metallurgical technologies and products will, nevertheless, accompany and interact with parallel developments in social complexity from the Chalcolithic to the Early Iron Age when, for the first time, metals seem to assume a full technomic role.